Involvement of Trichoderma harzianum Epl-1 Protein in the Regulation of Botrytis Virulence- and Tomato Defense-Related Genes - Gomes, Eriston V.; Ulhoa, Cirano J.; Cardoza, Rosa E.; Silva, Roberto N.; Gutiérrez, Santiago (Frontiers in Plant Science, 2017)
Several Trichoderma spp. are well known for their ability to: i) act as important biocontrol agents against phytopathogenic fungi; ii) function as biofertilizers; iii) increase the tolerance of plants to biotic and abiotic stresses; and iv) induce plant defense responses via the production and secretion of elicitor molecules. In this study, we analyzed the gene-regulation effects of Trichoderma harzianum Epl-1 protein during the interactions of mutant Δepl-1 or wild-type T. harzianum strains with: a) the phytopathogen Botrytis cinerea and b) with tomato plants, on short (24 h hydroponic cultures) and long periods (4-weeks old plants) after Trichoderma inoculation. Our results indicate that T. harzianum Epl-1 protein affects the in vitro expression of B. cinerea virulence genes, especially those involved in the botrydial biosynthesis (BcBOT genes), during the mycoparasitism interaction. The tomato defense-related genes were also affected, indicating that Epl-1 is involved in the elicitation of the salicylic acid pathway. Moreover, Epl-1 also regulates the priming effect in host tomato plants and contributes to enhance the interaction with the host tomato plant during the early stage of root colonization.